PROGRAM BOARDING SCHOOL DALAM MEMBANGUN KARAKTER KEPEMIMPINAN ISLAMI DI MAN 1 MOJOKERTO - Sitti Zuhrotul Fadilah Harvah; Erny Roesminingsih; Mufarrihul Hazin; Amrozi Khamidi (STKIP Pesisir Selatan, 2025)
In Law Number 20 of 2003 concerning National Education (UUSPN) Chapter II article 3 concerning the function of national education, it is stated that national education functions to develop the abilities and shape the character and civilisation of a dignified nation in order to educate the nation, with the aim of develop the potential of students to become people who are faithful and devoted to God the Almighty, have noble character, are healthy, knowledgeable, skilled, creative, independent and become democratic and responsible citizens. However, in reality, there are still many students who do not emphasise the above points, more specifically building Islamic leadership character. The purpose of this study is to discuss the role of boarding school programmes in building Islamic leadership character in a case study at MAN 1 Mojokerto. The method used in this research is a qualitative approach with a case study type. The results show that madrasahs can produce graduates who are able to lead when they enter their local communities, achieve more at the next level, have strengthened character values, religious moderation, and a strong national and Indonesian perspective. The competencies that students must possess, especially in boarding school programmes, include communication skills, decision-making skills, and team management skills.